The Identification and Functional Analysis of mRNA Localizing to Centrosomes - Zein-Sabatto, Hala; Lerit, Dorothy A. (Frontiers in Cell and Developmental Biology, 2021)
Centrosomes are multifunctional organelles tasked with organizing the microtubule cytoskeleton required for genome stability, intracellular trafficking, and ciliogenesis. Contributing to the diversity of centrosome functions are cell cycle-dependent oscillations in protein localization and post-translational modifications. Less understood is the role of centrosome-localized messenger RNA (mRNA). Since its discovery, the concept of nucleic acids at the centrosome was controversial, and physiological roles for centrosomal mRNAs remained muddled and underexplored. Over the past decades, however, transcripts, RNA-binding proteins, and ribosomes were detected at the centrosome in various organisms and cell types, hinting at a conservation of function. Indeed, recent work defines centrosomes as sites of local protein synthesis, and defined mRNAs were recently implicated in regulating centrosome functions. In this review, we summarize the evidence for the presence of mRNA at the centrosome and the current work that aims to unravel the biological functions of mRNA localized to centrosomes.